DETERMINAN PERILAKU 3M PADA MASA PANDEMI COVID-19DI KOTA SAMARINDA - Nurhasanah Nurhasanah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2022)
Behaviors of 3M is a mandatory behaviours to reduce the current rate transmission of covid-19 in this new normal era. This study aims to find out the determinant of 3M behaviors in Samarinda City. The study used a cross sectional design with 182 sampels used simple random sampling. The instrument was done google questionnaire form. Data analysis used chi square test. The result shows that 53% respondents are washing hand with a good category, 57% respondents had a bad behavior of physical distancing; 58% respondents had a good behaviour of wearing mask. The chi square test shows that p value for sex, age and level of education with washing hand, physical distancing, and wearing mask are 0,000; 0,03; 0,173; 0,804; 0,390; 0,04; 0,143; 0,135; 0,114. The conclusions of  this study are determinant of washing hand are sex and age meanwhile the determinant of physical distancing is education